Integrated palm oil mill effluent treatment and CO2 sequestration by microalgae - Nur Anira Syafiqah Hazman; Nazlina Haiza Mohd Yasin; Mohd Sobri Takriff; Hassimi Abu Hassan; Kamrul Fakir Kamarudin; Noor Irma Nazashida Mohd Hakimi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysian economy relies on palm oil industries as a driver for rural development. However, palm oil mill effluent (POME) that is generated from palm oil processing stages causes major environmental challenges. Before being released to the environment, POME treatment is crucial to comply with standard discharge limit. Microalgae have demonstrated excellent potential for phycoremediating POME and capturing CO2. In this study, local microalgae isolate such as Chlamydomonas sp. UKM 6 and Chlorella spp. UKM 8 were used for POME treatment in 21 days with different inoculum sizes (5%, 10% and 15%). In addition, an integrated treatment process was performed by taking the treated POME supernatant for cultivation of Chorella spp. UKM 2, Chorella sorokiniana UKM 3 and Chlorella vulgaris for CO2 sequestration study. Different CO2 concentrations (5%, 10% and 15%) were used and the experiments were carried out in 10 days under continuous illumination. The results showed that among two species involves in POME treatment, Chlamydomonas sp. UKM 6 showed a great potential to remove pollutant such as COD (56%), nitrogen (65%) and phosphorus (34%). The biomass after POME treatment and CO2 biofixation content high lipid (90 mg lipid/g biomass) which can be the potential source for biodiesel production. In CO2 sequestration study, C. sorokininana UKM3 able to takes up to 15% CO2 with CO2 uptake rate of 273 mgL-1d-1. In this study, the integrated system of POME treatment and CO2 sequestration were feasible using microalgae.